2004
DOI: 10.1242/jcs.01580
|View full text |Cite
|
Sign up to set email alerts
|

Role of myosin VIIa and Rab27a in the motility and localization of RPE melanosomes

Abstract: Myosin VIIa functions in the outer retina, and loss of this function causes human blindness in Usher syndrome type 1B (USH1B). In mice with mutant Myo7a, melanosomes in the retinal pigmented epithelium (RPE) are distributed abnormally. In this investigation we detected many proteins in RPE cells that could potentially participate in melanosome transport, but of those tested, only myosin VIIa and Rab27a were found to be required for normal distribution. Two other expressed proteins, melanophilin and myosin Va, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
159
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 135 publications
(179 citation statements)
references
References 59 publications
14
159
1
Order By: Relevance
“…Fusion of phagosomes with melanosomes is most prominently observed in cells overloaded with ROS or undigestable products (Orlow 1995;Schraermeyer et al 1999). Recent studies show that a large fraction of myosin-VIIa in primary RPE cells is found on melanosomal membranes (Gibbs et al 2004). Our studies with a new myosin-VIIa antibody have found that a population of myosin-VIIa also associates specifically with lysosomes, an organelle known to be required for ROS digestion.…”
Section: Discussionmentioning
confidence: 53%
See 4 more Smart Citations
“…Fusion of phagosomes with melanosomes is most prominently observed in cells overloaded with ROS or undigestable products (Orlow 1995;Schraermeyer et al 1999). Recent studies show that a large fraction of myosin-VIIa in primary RPE cells is found on melanosomal membranes (Gibbs et al 2004). Our studies with a new myosin-VIIa antibody have found that a population of myosin-VIIa also associates specifically with lysosomes, an organelle known to be required for ROS digestion.…”
Section: Discussionmentioning
confidence: 53%
“…Lysosome organization is maintained by the microtubule network with its motors, as has been shown for other cell types (Matteoni and Kreis 1987). Gibbs et al (2004) suggested that myosin-VIIa may play a role in short range movements and temporary tethering of melanosomes. Perhaps this is also true for myosin-VIIa found on lysosomes.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations